Elemen Pengurusan Personal Dalam Work Based Learning - Ali , Azita; Marwan , Hazlina (Online Journal for TVET Practitioners, 2019)
Graduates of quality and competence are essential criteria to enable them to gain a place in the job market. This puts pressure on higher education institutions in ensuring and understanding the skills that meet the industry’s demand for graduates to have a better career opportunity. Work Based Learning (WBL) is one of the platforms for students to gain a true working experience while also developing career management competencies in preparation for a good career start. The purpose of this study is to obtain expert opinion and expertise in identifying personal management elements for the development of career management competencies in WBL in polytechnics. The Fuzzy Delphi method (FDM) is used to obtain consensus among 16 WBL experts from various fields and backgrounds. The collection of research data is made using a questionnaire instrument given to the selected specialist. The findings show that the items in the personal management element of the condition, all items that have been consulted are organized according to priorities based on the expert’s suggestion.